When x^2 is added to x the sum is 42.

x^2 + x = 42

=> x^2 + x - 42 = 0

=> x^2 + 7x - 6x - 42 = 0

=> x(x + 7) - 6(x + 7) = 0

=> (x + 7)(x - 6) = 0

x = -7 and x = 6

**One possible value of x is -7.**

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now